Infection Risk-Adjusted Antibiotic Prophylaxis Strategies in Arthroplasty: Short Review of Evidence and Experiences of a Tertiary Center in Spain - Sanz-Ruiz P; Berberich C (Orthopedic Research and Reviews, 2020)
Pablo Sanz-Ruiz,1 Christof Berberich2 1Department of Orthopedics & Traumatology, University Hospital Gregorio Maranon, Madrid, Spain; 2Department of Medical Training, Heraeus Medical GmbH, Wehrheim, GermanyCorrespondence: Christof BerberichDepartment of Medical Training, Heraeus Medical GmbH, Philipp-Reis-Str. 8/13, Wehrheim 61273, GermanyTel +49 6181 352996Fax +49 6181 352916Email christof.berberich@heraeus.comAbstract: There is growing body of evidence that important patient-, procedure- and pathogen-related factors are linked to higher risks for prosthetic joint infections (PJI) following arthroplasty surgeries. The prior identification and optimization of such risk factors is considered paramount to minimize the incidence of these infections. Without any doubt, antibiotic prophylaxis remains one of the cornerstones among all preventive measures. However, the ideal antibiotic prophylaxis is still in debate and discussions have emerged, whether certain situations deserve adjustments or variations of the standard protocol taking into account antibiotic resistance surveillance data and patient risk factors for infections. This review aims to provide the reader with an overview of possible antibiotic prophylaxis strategies in response to these risks and discusses the clinical experiences so far obtained. We further present preliminary evidence that the use of a reinforced local antibiotic prophylaxis regimen with high-dose dual antibiotic-loaded bone cement may be an effective and easy-to-apply option in patients at high infection risks.Keywords: arthroplasty, prosthetic joint infection, antibiotic prophylaxis, risk for infection, risk-adjustment, extension of prophylaxis, dual prophylaxis, antibiotic-loaded bone cement